Computed tomographic evaluation of three types of screw trajectories for posterior cervical spine fixation: Cervical pedicle screw, lateral mass screw, and paravertebral foramen screw. Issue 28 (15th July 2022) - Tsuda, Keiichi; Tagami, Atsushi; Yamada, Shuta; Yokota, Kazuaki; Chiba, Ko; Yonekura, Akihiko; Tomita, Masato; Osaki, Makoto
Abstract : Computed tomography (CT) attenuation values of cervical spine were evaluated in vivo using a clinically relevant group. To compare CT attenuation values between cervical pedicle screw (CPS), lateral mass screw (LMS), and paravertebral foramen screw (PVFS) trajectories. CPS and LMS are commonly used for posterior fixation of the cervical spine. The PVFS method has been reported as a new method. CT attenuation values along the screw trajectory are reportedly associated with screw stability. We identified 45 patients who had undergone whole-body CT for trauma with no injury to the cervical spine. Regions of interest (ROIs) were designated along the trajectories that would be used for CPS, LMS, and PVFS through vertebral pedicles and lateral masses of the C3–C6 vertebrae. CT attenuation values of each ROI were measured and compared between each screw trajectories at each cervical vertebral level. Participants were divided into Group I (age, 20–39 years; n = 12), Group II (age, 40–59 years; n = 17), and Group III (age, 60–79 years; n = 16). CT attenuation values of ROIs were compared between each age group. PVFS trajectories showed higher CT attenuation values than LMS trajectories at every vertebral level and also higher values than CPS trajectories at C5 and C6 levels. CT attenuation values at C3 were lower than those at C4 in the LMS trajectory and lower than those at C5 and C6 in the PVFS trajectory. CT attenuation values were lower in the elder group (>60 years old) than in the other 2 groups for all screw trajectories. CT attenuation values suggested that the PVFS technique may be useful for posterior fixation of the cervical spine in elder patients who require more secure fixation.